Linguistic and axiological characteristics of regional identity topos (on the material of poetic discourse about Komsomolsk-on-Amur) - G A Shusharina (Russian Language Studies, 2014)
The author investigates poetry about Komsomolsk-on-Amur from the point of view of discourse theory. Local poets praise Far Eastern nature, its landscape, citizens' mentality. The above-noted characteristics make up linguistic and axiological domain of regional identity.